OPTIMIZATION OF REMAZOL RED DYE REMOVAL PERFORMANCE USING AEROBIC GRANULAR SLUDGE IN A SEQUENCING BATCH REACTOR - Sanjaya, Andri; Achmad, Feerzet; Robianto, Bagus; Ihsan, Ahyatul; Nugroho, Andreas Dwi; Alfares, Nelson; Damayanti, Damayanti; Fahni, Yunita; Deviany, Deviany; Saputri, Desi Riana (JURNAL INTEGRASI PROSES, 2025)
Textile wastewater pollution, mainly containing azo dyes such as Remazol Red, presents an environmental challenge in developing countries, including Indonesia. Although various wastewater treatment methods have been extensively studied, biological treatment efficiency at high dye concentrations remains challenging. In this context, aerobic granular sludge (AGS) technology in sequencing batch reactors (SBR) offers a potential solution. However, the existing knowledge gap lies in optimizing operating conditions for optimal dye degradation. This study demonstrates the use of response surface methodology (RSM) with a Box-Behnken design (BBD) to model the effects of independent variables such as aeration time, dye concentration, and COD on decolorization efficiency. Experimental results show that increasing aeration time and COD concentration significantly improve dye degradation, with an optimal decolorization value of 77% achieved at a COD concentration of 1000 mg/L and an aeration time of 24 hours. These findings imply that AGS-SBR technology can be further optimized for effective textile wastewater treatment on various industrial scales.